Factors Affecting Rapid Decline in Glomerular Filtration Rate in HIV/AIDS Patients Using Tenofovir Disoproxil Fumarate - Yuriandro, Prima; Yunihastuti, Evy; Marbun, Maruhum Bonar H; Nugroho, Pringgodidgo (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. Tenofovir disoproxil fumarate (TDF) treatment in HIV/AIDS patient has particular effect to the kidney, which is rapid decline in glomerular filtration rate (GFR) (> 5 cc/min/1.72 m2 one year after using the drug). The incidence rate for rapid decline in GFR and factors affecting it are still contradictive and not assessed completely. This study was done to identify cumulative incidence and factors affecting TDF related nephrotoxicity. Methods. A retrospective cohort study was conducted in HIV/AIDS outpatient clinic Cipto Mangunkusumo Hospital Jakarta. We included patients who start taking TDF as their medication from January 2010 until January 2015 with consecutive sampling method. Inclusion criterias were minimum one year of TDF treatment and baseline GFR > 60 cc/minute/1.72 m2. The study used secondary data from medical record, therefore subject with no GFR evaluation after one year was excluded. Logistic regression test was used to evaluate variabel that could potentially affect rapid decline in GFR. Results. 164 subjects were included for analysis and we found rapid decline in GFR after one year of TDF medication in 87 subjects (cumulative incidence 53%; 95% CI 45-60.4%). Factors affecting rapid decline in GFR were male gender (RR 4.0; 95% CI 1.1-4.8), CD4 cell count below 100 cell/mm3 (RR 3.7; 95% CI 1.7-8.1), weight increase above 20 % (RR 4.0; 95% CI 1.0-4.8), and baseline GFR above 90 cc/min/1.72 m2 (RR 9.8; 95% CI 2.3-42.1). Conclusion. The incidence rate for rapid decline in GFR after a year of TDF medication in HIV/AIDS patients in Cipto Mangunkusumo hospital was 53%. Risk factors that affecting this nephrotoxicity were male gender, CD4 cell count below 100 cell/mm3, weight increase above 20%, and baseline GFR above 90 cc/min/1.72 m2.